Manajemen Pemasaran Jasa Pendidikan dalam Menarik Peserta Didik Baru di MI Melalui Hubungan Masyarakat - Ja’far (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research aims to determine the marketing management of educational services in attracting new students at MI Roudlotul Mubtadiin through public relations. The research method uses a descriptive qualitative approach, namely by describing and explaining the marketing management of educational services in attracting new students at MI Roudlotul Mubtadiin through public relations. Marketing of educational services at MI Roudlotul Mubtadiin in attracting new students uses a marketing mix, namely: providing integrated skills and knowledge to students, free registration fees and tuition fees, a comfortable, safe and suitable location for carrying out the teaching and learning process, promotion through communication and networking. relations with the community, have supporting and adequate infrastructure, the learning process follows the Madrasah curriculum/government curriculum. Public relations management in attracting new students at MI through community relations, namely carrying out national holiday commemorations involving the entire community, next are events commemorating Islamic holidays, compensation for orphans, birthdays in the month of Rabiul Awal, visiting almost all students, parents of students who are illness, condolences to all students, students' families, communities around MI who have died and visits by institutional leaders to local communities who are less fortunate in order to receive scholarships or discounts on funding.